Potential role of organic matters and phosphate-solubilizing bacteria on growth of mungbean (Vigna radiata) and their response to management of phytonematodes - TIYAGI, S A; MAHMOOD, I; KHAN, Z; RIZVI, R (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 2007–09 to eplore addition of organic matters and phosphate-salubilizing bacteria (PSB) to soil as an alternative means of organic management of nematodes under field condition at Aligarh, Uttar Pradesh. Organic matters in the form of oilseed cakes of neem (Azadirachta indica Adr. Juss.), castor (Ricinus communis L.), groundnut (Arachis hypogaea L.), linseed (Linum usitatissimum) and sunflower (Helianthus annuus L.) were found to be highly efficacious in reducing the multiplication of plant-parasitic nematodes Meloidogyne incognita (Kofold & White) Chitwood, Rotylenchulus reniformis Limnford & Oliveira, Tylenchorhynchus brassicae, etc. The plant growth parameters such as plant weight, pollen fertility (%), pods/plant, root-nodulation and chlorophyll content of mungbean [Vigna radiata (L.) R. Wilczek] increased significantly. The multiplication rate of phyto-nematodes and number of root- galls caused by M. incognita greatly affected in the presence of Pseudomonas fluorescens (Trevisan) Migula as compared to its absence. Damage caused by the nematodes was further reduced when Pseudomonas fluorescens was added along with the oilseed cakes. Neem-cake was found most effective in combination with Pseudomonas fluorescens.